Preface to theme issue 'Modelling infectious disease outbreaks in humans, animals and plants: epidemic forecasting and control' - Thompson, R; Brooks-Pollock, E (Royal Society, 2019)
This preface forms part of the theme issue 'Modelling infectious disease outbreaks in humans, animals and plants: epidemic forecasting and control'. This theme issue is linked with the earlier issue 'Modelling infectious disease outbreaks in humans, animals and plants: approaches and important themes'.